The enduring art of Japan - Warner, Langdon (Harvard University Press, 1952)
Study of the fine arts illuminates the history of a race with a peculiarly significant glow and history in its turn provides the light by which art can be viewed. Perhaps, even with so few photographs and such a brief text as a small book allows, one may contrive to suggest a binocular vision of the past.